Studi Kelayakan Pengembangan Bisnis Penggilingan Padi Cianjur Studi Kasus PB. X - Mugni Septian; A. Harits Nu'man (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Feasibility study on the legal aspect are known PB. X does not yet have complete licensing documents and is currently declared unfit for development, the environmental aspect, PB. X has had a positive economic impact on the surrounding environment and was declared feasible. PB. X was declared eligible with the forecasting results show an increasing trend of product demand from market aspect, the aspect of management was declared eligible, because he had run a good management system. Results of the technical aspects, the break event point calculation show the break-even point at the total production of 7714 kilograms and can be declared feasible, with the estimated production volume still within the capacity and technical capabilities. The results of the investment criteria assessment with the 2 condition schemes of not buying assets and buying assets. The decision to purchase or not to purchase assets has its own advantages and disadvantages, if the purchase of assets is made then he has certainty for the continuity of business activities compared to the rental system, but it has a huge impact on the company's finances, then PB. X was declared eligible based on financial aspects. The results of the overall business feasibility study, stated that PB. X must complete licensing documents to be able to carry out the development bussines plan. The results of the sensitivity analysis show that PB. X finances is very sensitive to changes in material costs, production volume, selling prices, and changes in income. Abstrak. Studi kelayakan pada aspek hukum diketahui PB. X belum memiliki dokumen perizinan yang lengkap dan saat ini dinyatakan tidak layak untuk dikembangkan, berdasarkan aspek lingkungan, PB. X telah memberikan dampak ekonomi yang positif bagi lingkungan sekitar dan dinyatakan layak. PB X dinyatakan layak dengan hasil peramalan menunjukkan tren peningkatan permintaan produk dari segi aspek pasar, aspek manajemen PB. X dinyatakan layak, karena telah menjalankan sistem manajemen yang baik. Hasil dari aspek teknis, perhitungan break event point menunjukkan titik impas pada total produksi 7714 kilogram dan dapat dinyatakan layak, dengan perkiraan volume produksi masih dalam batas kapasitas dan kemampuan teknis. Hasil penilaian kriteria investasi dengan 2 skema kondisi tidak membeli aset dan membeli aset. Keputusan untuk membeli atau tidak membeli aset memiliki kelebihan dan kekurangan tersendiri, jika pembelian aset dilakukan maka memiliki kepastian kelangsungan kegiatan usaha dibandingkan dengan sistem sewa, tetapi berdampak besar pada keuangan perusahaan, maka PB. X dinyatakan layak berdasarkan aspek finansial. Hasil studi kelayakan usaha secara keseluruhan, menyatakan PB. X harus melengkapi dokumen perizinan untuk dapat menjalankan rencana pengembangan bisnis. Hasil analisis sensitivitas menunjukkan bahwa keuangan PB, X sangat sensitif terhadap perubahan biaya material, volume produksi, harga jual, dan perubahan pendapatan.